Scripture and Society: Quranic Ethics in the Age of Globalization - Saliha Kanwal; Hafiz Fahad Aziz (`, 2025)
The paper discusses the significance and the use of Quranic ethics in solving the modern global issues confronting the Muslim communities in the era of fast globalization. Globalization is not only an ethical opportunity and a dilemma as economic, cultural and moral orders are being restructured. This paper looks into the principles of Quranic ethics like justice (adl), compassion (rahmah), trust (amanah), and God-consciousness (taqwa), and the relevance of these values in providing moral engagement in pluralistic societies. It examines some of the most important social matters such as economic inequality, environment degradation, and human rights and how the teachings of the Quran support social justice, the environment, and dignity of all humans. The article also talks about the Quran supporting moral pluralism by its command of mutual understanding and collaboration of nations. These ethical values, however, are questioned by internal forces like interpretive rigidity, a politicized outlook of religion as well as external forces like Islamophobia and the secular spearheading of world affairs. The role of the reform-minded scholars, civil society, and digital platforms in restoring the Quranic ethics to a contemporary context is highlighted in the paper. Finally, it claims that the moral instruction of the Quran by no means limited to inner spirituality can provide a relevant and principled answer to the ethical dilemmas of the contemporary globalization and help to create a more equitable, inclusive and spiritually oriented international system. Keywords: Qur’anic Ethics, Globalization, Islamic Morality, Social Justice, Environmental Stewardship, Human Rights, Ta‘Aruf, Pluralism, Muslim Societies, Interfaith Dialogue